Scratch Testing of Coarse-Grained and Ultra Fine-Grained Copper; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Fortuna S. V.; Podgornykh O. A. Oleg Anatolievich; Shamarin N. N. Nikolay Nikolaevich; Filippova E. O. Ekaterina Olegovna (2018, 2018)
Title screen